STUDYING KNOWLEDGE ABOUT COVID - 19 HEALTH CARE BEHAVIOR AND GUIDELINES FOR SELF-PROTECTION OF SECONDARY SCHOOL STUDENTS IN THE COVID - 19 SITUATION UNDER THE JURISDICTION OF THE SECONDARY EDUCATIONAL SERVICE AREA OFFICE - Onto, Patcharuch; Rattanasumrit, Nareerom; Wataneeyawech, Thitima; Suthisak, Onthira; Kongmuang , Chatpong (Journal of MCU Nakhondhat, 2023)
This research aimed to 1) study knowledge in COVID - 19 2) study health care behavior and 3) study guideline for self - protection in the COVID - 19 situation of secondary school students in secondary educational service area.The descriptive research design was used in this study. The population were secondary school students under the jurisdiction of the secondary educational service area office and samples were 499 students calculate from Taro Yamane table of sample sizes and were sampling from 4 province in Nakhon Sawan, Uthai Tanee, Pichit, and Kamphangphet.The research instrument was “The Questionnaire of Knowledge, Health Care Behavior and Guideline for Self - protection of Secondary School Students in the COVID - 19 Situation”, that new develop with content validity was at .80 and the reliability score was at .87. Data were collected by research team and were analyzed by computer package to analyze with descriptive statistic. The results of this research were as follow: Most students had good knowledge in COVID - 19 in the topic of diffusion (97.9%), signs of disease (97.9%) and incubation period (96.9%) Level of Knowledge was at high level (61.56%), moderate level (34.92%) and low level (3.52%) as follow.The most 3 ranks of health care behaviors were mask wearing ( = 4.85), temperature monitoring ( = 4.64), and hand washing ( = 4.45). Guideline for self - protection were need mask for free, support of knowledge and practice, quality vaccine and ATK for service, and timely treatments. These results may benefit to set the guideline for disease prevention, and any supports in future.